2008
DOI: 10.1007/s12275-008-0032-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities in the initial stage of marine biofilm formation on artificial surfaces

Abstract: Succession of bacterial communities during the first 36 h of biofilm formation in coastal water was investigated at 3 approximately 15 h intervals. Three kinds of surfaces (i.e., acryl, glass, and steel substratum) were submerged in situ at Sacheon harbor, Korea. Biofilms were harvested by scraping the surfaces, and the compositions of bacterial communities were analyzed by terminal restriction fragment length polymorphism (T-RFLP), and cloning and sequencing of 16S rRNA genes. While community structure based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
133
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(150 citation statements)
references
References 23 publications
11
133
2
4
Order By: Relevance
“…It is possible, however, that other, more subtle effects may have roles in determining phyllosphere population structure. Temporal succession patterns are known to occur in aquatic biofilm systems (24,27) and have been shown in the phyllosphere of the cottonwood (Populus deltoides) (39). Unlike the aquatic situations, where the biofilms were forming on abiotic surfaces, we have shown that phyllosphere populations are influenced by leaf characteristics.…”
Section: Discussionmentioning
confidence: 60%
“…It is possible, however, that other, more subtle effects may have roles in determining phyllosphere population structure. Temporal succession patterns are known to occur in aquatic biofilm systems (24,27) and have been shown in the phyllosphere of the cottonwood (Populus deltoides) (39). Unlike the aquatic situations, where the biofilms were forming on abiotic surfaces, we have shown that phyllosphere populations are influenced by leaf characteristics.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, it has been shown that bacterial community composition and density of the surrounding water (24) play an important role for biofilm establishment. In this context, Dang and Lovell (25,26) demonstrated that the marine Rhodobacter group not only dominates early stages of biofilm formation on artificial surfaces but also is highly abundant as a potential surface colonizer in coastal seawater all year round (27).…”
mentioning
confidence: 99%
“…On the other hand, biofilms can be detrimental to the surfaces of man-made structures such as ships and bridges in aquatic environments (Gaylarde and Morton, 1999;Dang and Lovell, 2000;Flemming, 2002). Due to such profound importance of biofilms in ecology and industry, many studies have been performed on the bacterial communities, developmental processes, and physiology of biofilms in various aquatic environments, and methods to control biofilm formation have been developed (Gaylarde and Morton, 1999;Dang and Lovell, 2000;Armstrong et al, 2001;Molin and Tolker-Nielsen, 2003;Jones et al, 2007;Egan et al, 2008;Lee et al, 2008).…”
Section: 미생물학회지 제52권 제1호mentioning
confidence: 99%
“…In addition, investigating the composition and diversity of early microbial colonizers during biofilm formation in natural marine environments of Antarctica is challenging due to the practical problem of conducting experiment in cold environments. Previous studies on microbial community changes during biofilm development had been performed in natural environments of temperate areas by using fingerprinting techniques (Moss et al, 2006;Jones et al, 2007;Lee et al, 2008;Pohlon et al, 2010;Salta et al, 2013), which suffer from a low taxonomic resolution. Thus, application of next-generation sequencing technology that allows the better characterization of the unseen realm is required for the analysis of unexplored bacterial community of biofilm formed in Antarctic marine environments.…”
Section: 미생물학회지 제52권 제1호mentioning
confidence: 99%
See 1 more Smart Citation